Prehodni pojavi pri postopku brušenja - Vekteris, Vladas (Strojniški vestnik, 2005)
Local contact displacements resulting from the elastic deformation of the tooland the blank, were studied using the finite-element and by experiments. Graphical and analytical expressions for the cutting force, with harmonical and stochastic components, were obtained. Previously published research on thebehaviour of the contact between the grinding wheel and the workpiece has been based, on the assumption that the contact deformations represent a directfunction of both the normal and the tangent forces acting on the wheel or its grains during the grinding process, without taking into account the attrition and breaking of the grains. This paper covers the procedure for researching and graphically representating transient processes and the patternof the abrasive grainsć destruction within the contact zone under impulse loads, which is based on the method of finite elements and the resultsof a high-speed circular plunge-grinding experiment. The above-mentioned method can be applied to elastic, inelastic, plastic and othernonlinear materials machined by grinding. To introduce the nonlinear properties of the material in the experiment, the modulus of the volume and the modulus of the shift in the contact zone between the grinding wheel (grade24A12INI28E5) and the workpiece (steel 45) are simulated by three-parametric elements. The presented method makes it possible to calculatetransient stress and deformations during high-speed circular plunge grinding and to study the destruction of abrasive grains in a two-dimensional medium with indefinite boundaries and nonlinear characteristics. The present research is aimed at finding out the influence of transient phenomena on the structure of the cutting force during the process of grinding.
Keywords: postopki brušenja; napetosti; deformacije; simuliranje; analize eksperimentalne; brušenje; mehanske lastnosti